Characterizing the variability of natural gas hydrate composition from a selected site of the Western Black Sea, off Romania. (February 2021) - Chazallon, B.; Rodriguez, C.T.; Ruffine, L.; Carpentier, Y.; Donval, J.-P.; Ker, S.; Riboulot, V.
Abstract: Natural Gas Hydrates (NGH) collected during the Ghass cruise 2015 in the Western Black Sea onboard the R/V Pourquoi pas? are characterized by a suite of techniques. Gas Chromatography and Raman spectroscopy are used for the identification of the nature of the gas source, the hydrate structure and spatial variability of cage occupancies. The nature and source of hydrate forming gases primarily reveal a high methane content (99.6 mol%) and small amount of nitrogen (>0.29 mol%) and CO2 (0.056 mol%). Isotopic analyses from the hydrate-bound methane and recently published results from Pape et al. (2020) clearly indicate a microbial source of gas supplying the hydrate deposit generated by the reduction of carbon. For the first time, Raman imaging spectroscopy was applied on NGH recovered in the Western Black Sea. The results show a heterogeneous distribution of the encapsulated guest molecules (CH4, N2 and H2 S), which is associated with a spatial variability of the guest-gas composition at the micron-scale. Some portions of the 2D-Raman images clearly exhibit a relative N2 -enrichment (with a concentration exceeding 6 mol% N2 at some positions), while H2 S shows a rather minor contribution on all the spectral maps investigated. A correlation is then established between the composition of the gas in the NGH and its impact on the CH4 cage occupancy, with a ratio of θLC /θSC (large cage/small cage) between ~ 0.5 and 1.26 depending on the positions analyzed. The departure from the expected ratio in pure methane hydrate is attributed to the preferential encasement of N2 in the large cage of the NGH structure. In addition, the occurrence of carotenoids identified in sediment-rich zones show a minor impact on the CH4 cage occupancies. The results are discussed within the context of natural gas resource estimates in NGH to emphasize how the measured cage occupancies may impact the volumetric conversion factor commonly used with other geologic parameters to determine the resource endowment and global volume of methane. The small-scale heterogeneities revealed by the 2D-Raman images point out the importance to better understand stages of hydrates formation in methane-rich seafloor environment. Highlights: NGH from Black Sea are investigated by gas chromatography and Raman spectroscopy. The hydrates are structure sI and contain mainly CH4 and small amounts of N2 and CO2 . CH4 being generated by the reduction of CO2 . 2D-Raman reveals spatial variability in guests' distribution and hydrate composition. Raman imaging analysis shows a spatial variability of the cage occupancy.